Analytical calculation of the RFOC method in single-phase induction motor - Jannati, M. (2016)
This study discusses the different techniques for speed control of single-phase induction motor with two asymmetrical main and auxiliary windings based on Rotor Field-Oriented Control (RFOC) method. In the presented methods, transformation matrices are introduced and applied to the equations of single-phase induction motor. It is shown by applying these rotational transformations to the unbalanced equations of single-phase induction motor, equations of single-phase induction motor are transformed into symmetrical equations. These rotational transformations are achieved based from the steady-state equivalent circuit of single-phase induction motor. Finally, a method for RFOC of single-phase induction motor is proposed. Results show the good performance of the proposed method.